Family functioning but not social capital is associated with better mental health in adolescents affected by violence and displacement by armed conflict in Colombia (2021)
Background: The effect of the Colombian armed conflict on the mental health of adolescents is still poorly understood. Aims: Given social interventions are most likely to inform policy, we tested whether two potential intervention targets, family functioning and social capital, were associated with mental health in Colombian adolescents, and whether this was moderated by experience of violence and displacement. Methods: We examined the cross-sectional association between family functioning, cognitive social capital, structural social capital and 12-month prevalence of Composite International Diagnostic Interview (CIDI) diagnosed psychiatric disorder, using data on 12 to 17-year-old adolescents (N=1,754) from the 2015 National Mental Health Survey of Colombia, a nationally representative epidemiological study. We tested whether associations survived cumulative adjustment for demographic confounders, experience of non-specific violence and harm and displacement by armed conflict. Results: Neither structural nor cognitive social capital were associated with better mental health. Better family functioning was associated with reduced risk of poor mental health in an unadjusted analysis (OR 0.90 [0.85–0.96]), and after cumulative adjustments for demographic confounders (OR 0.91 [0.86–0.97]), non-specific violence and harm (OR 0.91 [0.86–0.97]) and social capital variables (OR 0.91 [0.85–0.97]). In the final model, each additional point on the family APGAR scale was associated with a 9% reduced odds of any CIDI diagnosed disorder in the last 12 months. Conclusions: Better family functioning was associated with better mental health outcomes for all adolescents. This effect remained present in those affected by the armed conflict even after accounting for potential confounders.